1970
DOI: 10.31729/jnma.219
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Cause of Unilateral Epistaxis: Nasal Leech Infestation

Abstract: Common causes for unilateral nasal bleeding in adults are benign or malignant tumors and deviatednasal septum. Here we present two cases of recurrent unilateral nasal bleeding due to leech infestation.Though it is not a common cause for nasal bleeding, a clinician should suspect leech infestation for arecurrent nasal bleeding specially in tropical countries like Nepal.Key words: leech infestation, nasal bleeding, unilateral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Moreover, leech infestation may be observed in the nose, nasopharynx, and eye. Ghimire et al (9) reported a unilateral nostril epistaxis caused by leech infestation. Bilgen reported leech-caused recurrent epistaxis during 4 months (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, leech infestation may be observed in the nose, nasopharynx, and eye. Ghimire et al (9) reported a unilateral nostril epistaxis caused by leech infestation. Bilgen reported leech-caused recurrent epistaxis during 4 months (10).…”
Section: Discussionmentioning
confidence: 99%
“…The saliva of leeches contain several anticoagulants and a histamine, such as a vasodilator, which are useful for providing critical venous outflow for compromised tissue replants (14). Biologically active substances improve blood circulation in the organs; serve as a thrombolytic, anti-inflammatory substance; stimulate immunity promote tissue nutrition; and strengthen the immune systems (9).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is recommended that a clinician should always suspect leech infestation for recurrent nasal bleeding in Tropics and it is always important to examine both the nasal cavities [9,10]. The usual time period (delay) between leech infestation and onset of [6] and the common symptoms are recurrent epistaxis, blood spitting, odynophagia, dysphagia, dyspnoea and at times hemoptysis, depending upon the various sites of infestation [11]. The endoparasitism usually persists for a long time before actual intervention by a clinician, because of the inconspicuous site of infestation and the absence of pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are no reports of vinegar toxicity in the dog. In humans, various techniques have been used to detach leeches from mucous membranes, including suction (Adhikari ), normal saline (Hannan and Hoque ), lidocaine (Ghimire and Acharya ), forceps with or without bipolar electro‐cautery (Chen et al . ) and vinegar (Bilgen et al .…”
Section: Discussionmentioning
confidence: 99%